(untitled) (Research, Society and Development, 2022)
Introduction: The Covid-19 pandemic has influenced many health determinants, in which violence against women stands out. This important determinant was impacted by the isolation of the pandemic in the world and the appearances for its containment, such as social isolation. Objective: To analyze, in the international and national literature, the influence of factors arising from the context of COVID-19 on domestic violence against women, including social isolation. Method: This is an Integrative Literature Review (RIL) on the Latin American and Caribbean Health Sciences Literature (LILACS), Education Resources Information Center (ERIC) and PubMed databases. Results: 325 were identified, 158 from ERIC, 164 from PubMed and 4 from LILACS. These only 15 articles were reported to RIL. Discussion: The perpetration of violence against women during crises is not an exclusive factor of the contemporary Pandemic, however it has already been observed in other disasters. Factors specific to the pandemic context, such as social isolation, have alarmed some types of violence more than others, as in the case of psychological violence. Conclusion: It was considered necessary to put the fight against domestic violence against women as a key factor in the fight against the pandemic, directing health and support services to this end, coming from mitigating factors arising from the financial and social crisis that increases their vulnerability.